A giant radio bridge connecting two galaxy clusters in Abell 1758. (22nd August 2020) - Botteon, A; van Weeren, R J; Brunetti, G; de Gasperin, F; Intema, H T; Osinga, E; Di Gennaro, G; Shimwell, T W; Bonafede, A; Brüggen, M; Cassano, R; Cuciti, V; et al.
ABSTRACT: Collisions between galaxy clusters dissipate enormous amounts of energy in the intracluster medium (ICM) through turbulence and shocks. In the process, Mpc-scale diffuse synchrotron emission in form of radio haloes and relics can form. However, little is known about the very early phase of the collision. We used deep radio observations from 53 MHz to 1.5 GHz to study the pre-merging galaxy clusters A1758N and A1758S that are ∼2 Mpc apart. We confirm the presence of a giant bridge of radio emission connecting the two systems that was reported only tentatively in our earlier work. This is the second large-scale radio bridge observed to date in a cluster pair. The bridge is clearly visible in the LOFAR image at 144 MHz and tentatively detected at 53 MHz. Its mean radio emissivity is more than one order of magnitude lower than that of the radio haloes in A1758N and A1758S. Interestingly, the radio and X-ray emissions of the bridge are correlated. Our results indicate that non-thermal phenomena in the ICM can be generated also in the region of compressed gas in-between infalling systems.